Nicotinism and the knowledge of consequences of laryngectomy among university students. - Hamerlińska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Nicotine addiction is currently one of the most serious health and social problems worldwide, which contributes to the development of numerous diseases, including, above all, laryngeal cancer, which may lead to laryngectomy. The consequences of losing one’s larynx are irreversible. The objective of the study presented in this paper was to describe the knowledge of the consequences of radical laryngectomy among students pursuing a variety of majors. The study covered 194 people (119 non-smokers and 75 smokers), who took part in diagnostic survey based on a bespoke questionnaire. Based on the study in question, the author determined that the level of knowledge about the consequences of laryngectomy among the majority of students is average to low, while smoking students have an average awareness of these consequences. Moreover, it turned out that age, gender, major and the number of smokers in students’ closest circles do not determine the knowledge about the subject at hand. The results of the study indicate that the anti-smoking public service campaigns addressed to youth should include information about both the risk of diseases and their consequences, which may significantly reduce the quality of life and hinder everyday functioning.